Plasmalogens and Photooxidative Stress Signaling in Myxobacteria, and How it Unmasked CarF/TMEM189 as the Δ1′-Desaturase PEDS1 for Human Plasmalogen Biosynthesis - Padmanabhan, S.; Monera-Girona, Antonio J.; Pajares-Martínez, Elena; Bastida-Martínez, Eva; del Rey Navalón, Irene; Pérez-Castaño, Ricardo; Galbis-Martínez, María Luisa; Fontes, Marta; Elías-Arnanz, Montserrat (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens are glycerophospholipids with a hallmark sn-1 vinyl ether bond that endows them with unique physical-chemical properties. They have proposed biological roles in membrane organization, fluidity, signaling, and antioxidative functions, and abnormal plasmalogen levels correlate with various human pathologies, including cancer and Alzheimer’s disease. The presence of plasmalogens in animals and in anaerobic bacteria, but not in plants and fungi, is well-documented. However, their occurrence in the obligately aerobic myxobacteria, exceptional among aerobic bacteria, is often overlooked. Tellingly, discovery of the key desaturase indispensable for vinyl ether bond formation, and therefore fundamental in plasmalogen biogenesis, emerged from delving into how the soil myxobacterium Myxococcus xanthus responds to light. A recent pioneering study unmasked myxobacterial CarF and its human ortholog TMEM189 as the long-sought plasmanylethanolamine desaturase (PEDS1), thus opening a crucial door to study plasmalogen biogenesis, functions, and roles in disease. The findings demonstrated the broad evolutionary sweep of the enzyme and also firmly established a specific signaling role for plasmalogens in a photooxidative stress response. Here, we will recount our take on this fascinating story and its implications, and review the current state of knowledge on plasmalogens, their biosynthesis and functions in the aerobic myxobacteria.